Preliminary Selection of Potential Probiotic Lactic Acid Bacteria Isolated from Cocoa Beans (Theobroma cacao) - Amarantini, Charis; Prakasita, Vinsa Cantya; Sema, Maria Trivonia (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This study aims to isolate and identify LABs that spontaneously grow fermented cocoa beans that have the potential as probiotics. The isolation was carried out selectively using an MRS agar medium supplemented with 1% CaCO3. LAB's potential as a probiotic was selected based on the acid resistance test, bile salt resistance test, and antimicrobial activity test. The results showed that three isolates of lactic acid bacteria, namely strains K1B1, K2T2, and K3B4 were tolerant of gastric acid's pH conditions (pH 2.5, pH 3, and pH 4). They also can survive the bile salts (0.3%, 0, 5%, and 1%) and have antibacterial characteristics. The three isolates were identified as Lactobacillus Plantarum species (ID 99.9%).